2016
DOI: 10.3168/jds.2015-10601
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the liver X receptor-dependent regulatory mechanism of goat stearoyl-coenzyme A desaturase 1 gene by linoleic acid

Abstract: Stearoyl-coenzyme A desaturase 1 (SCD1) is a key enzyme in the biosynthesis of palmitoleic and oleic acid. Although the transcriptional regulatory mechanism of SCD1 via polyunsaturated fatty acids (PUFA) has been extensively explored in nonruminants, the existence of such mechanism in ruminant mammary gland remains unknown. In this study, we used goat genomic DNA to clone and sequence a 1,713-bp fragment of the SCD1 5' flanking region. Deletion assays revealed a core region of the promoter located between -415… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…Indeed, in both species, LXRA and PPARA were significantly and negatively associated (−0.70 < r < −0.32, n = 21) with almost all the other genes, whereas significant and positive associations (+0.32 < r < +0.87, n = 22) were observed for SREBF1 and SP1, respectively, suggesting a putative implication in the repression and induction of the genes by these transcription factors, which is in line with several studies in bovines (Bionaz and Loor, 2008;Kadegowda et al, 2009;Oppi-Williams et al, 2013) and caprines (Shi et al, 2013;Xu et al, 2016;Yao et al, 2016) that reported crucial roles of these transcription factors on lipogenic gene expression. Such relationships might result from shared regulation by the same transcription factor or from concomitant regulation by different transcription factors (Harvatine and Bauman, 2006) for these genes, regulation involving microRNA (Lynn, 2009), or other mechanisms.…”
supporting
confidence: 72%
“…Indeed, in both species, LXRA and PPARA were significantly and negatively associated (−0.70 < r < −0.32, n = 21) with almost all the other genes, whereas significant and positive associations (+0.32 < r < +0.87, n = 22) were observed for SREBF1 and SP1, respectively, suggesting a putative implication in the repression and induction of the genes by these transcription factors, which is in line with several studies in bovines (Bionaz and Loor, 2008;Kadegowda et al, 2009;Oppi-Williams et al, 2013) and caprines (Shi et al, 2013;Xu et al, 2016;Yao et al, 2016) that reported crucial roles of these transcription factors on lipogenic gene expression. Such relationships might result from shared regulation by the same transcription factor or from concomitant regulation by different transcription factors (Harvatine and Bauman, 2006) for these genes, regulation involving microRNA (Lynn, 2009), or other mechanisms.…”
supporting
confidence: 72%
“…The results obtained with vectors expressing the factor series NFY-A, -B, -C are also in line with the respective literature in that we observed in the HepG2 model for liver cells a significant stimulation (cf [ 24 ]) and slight repression in the MAC-T model for MEC, similar as recently reported using the human breast cancer line MCF7 [ 59 ]. The pivotal role of the NFY factor family for the basal and nutritional regulated activity of the SCD1 promoter has recently been underscored in goat MEC model cells [ 60 ]. We had included into this set of experiments vectors expressing the NF-κB p50 and −p65 factors not least because of the close vicinity of their cognate promoter binding site to each other and that of C/EBP factors.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Scd1 expression and activity are directly or indirectly regulated by a wide range of transcription factors, including Srebp1c, Lxrα, Pparγ, C/EBP‐α, NF‐1, NF‐Y, AP‐1, Sp1, thyroid hormone receptor, and peroxisome proliferator–activated receptor gamma coactivator 1‐α . Using an online database and comparing our results with a previous study, we also identified some putative Srebp1 (SRE), Pparγ, C/EBP, Lxr, NF‐Y, and Sp1 binding sites. A luciferase assay showed that overexpression of Srebp1 and Pparγ produced a 2‐fold increase in the activity of the scd1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that Cd might regulate the expression of scd1 through Srebp1. Similarly, this mechanism is responsible for polyunsaturated fatty acids/cholesterol‐mediated scd1 expression in mammals . In mammals, Srebp1 has been indicated to regulate the expression of Scd1 through an SRE in its promoter region .…”
Section: Discussionmentioning
confidence: 99%